Mapping of GIS-Flood Hazard Using the Geomorphometric-Hazard Model: Case Study of the Al-Shamal Train Pathway in the City of Qurayyat, Kingdom of Saudi Arabia - Ashraf Abdelkarim; Seham S. Al-Alola; Haya M. Alogayell; Soha A. Mohamed; Ibtesam I. Alkadi; Ismail Y. Youssef (Geosciences, 2020)
Drainage basins in dry and semiarid environments are exposed to sudden, irregular flooding that poses a threat to urban areas and infrastructure. The associated risk is exacerbated by land use changes. Geomorphometric analyses of drainage basins based on geographic information systems (GIS) are essential tools for assessing conceptual flood hazards. Geomorphological data extracted from high-precision digital elevation models (DEMs) provide valuable information for modeling the geomorphic, surface classifications of the earth, and for flood hazard mapping. This study aimed to develop an integrative approach to the mapping of flood hazards along the Al-Shamal train pathway in the city of Qurayyat in the Kingdom of Saudi Arabia (KSA) using GIS and hazard modeling for geomorphological ranking. Furthermore, we propose strategic solutions to provide mitigation and protection from negative impacts with the aim of improving the level of awareness of flood geomorphology. The hazard model of geomorphological ranking was used in mapping and calculating the degree of hazards using 24 geomorphometric criteria. These criteria were divided into formal criteria, terrain criteria, and criteria related to the drainage network. The results of the study revealed that the drainage sub-basins are exposed to flood hazards along the Al-Shamal train pathway in the city of Qurayyat. The very high flood hazard constituted 4228.3 km2, accounting for 70.3% and 65.7%, respectively, of the drainage basins of the wadis of Makhrouq and Bayer. The high flood hazard represented 61% (4712.4 km2) of the basin of the wadis of Sarmadaa. The medium flood hazard was concentrated in the drainage basin of the wadi of Hasidah, accounting for nearly 57.7% (1271.3 km2). The very low flood hazard was present in 46.5% of the drainage basin of the wadis of Hasidah Umm Nakhla, accounting for an area of 799.4 km2. The methodology applied in this study can be used in the estimation of flood hazards in different drainage basins throughout Saudi Arabia and in similar arid regions.